Preimplantation genetic diagnosis – numerical chromosome abnormalities in fertilized human oocytes after TESA - Širůčková, K; Kosařová, Marcela; Zudová, Dagmar; Brachtlová, Tereza; Bürgerová, E (Abstracts of the 2nd Czech and International Congress of Andrology, 2007)
In sperms of infertile men is higher incidence of chromosome aneuploidy. Consequently for embryos developed from these sperms PGD is indicated. Material and methods: In our laboratory were made 331 PGD cycles. 25 of them were counted among group of indication, in which embryos were fertlized with sperm after TESA. PGD was performed on blastomeres from three-day old embryo in two hybridisation cycles. During this procedure we evaluated 8 chromosomes (13, 15, 16, 18, 21, 22, X, Y). Results: Total mean age of patients with spermatogenic failure was 32.24. This group contained 25 couples and 184 embryos were evaluated. From this amount 75 preimplantation embryos did not show numerical aberrations for detected chromosomes and 22 of them were transferred. 31.8 % patients were pregnant (this number related to embryotransferr). On the other side more than 59 % investigated blastomeres showed a numerical chromosomal abnormality. Monosomy chromosome 16 and aneuploidy of sex chromosomes were observed the most frequently. Conclusions: The incidence of aneuploidies in sperm after TESA should correlate with incidence of genetic abnormalities in embryo. Our results are similar to literature, where sex chromosomes aneuploidies the most frequently occur in sperms after TESA. In these studies the chromosome 16 was not analysed. The higher incidence of monosomy of this chromosome can be caused by low number of evaluated blastomeres.